Impact of Financial Literacy, Risk Tolerance, Usefulness Perception, and Trust Perception on Financial Decision of MSMEs in West Java - Kartiwa, Aa; Hidayat, Gustina; Lisbet, Zeanette T; Siagian, Ade Onny (IJBLE Scientific Publications Community Inc., 2024)
This study investigates the impact of financial literacy, risk tolerance, perceived usefulness, and trust perception on the financial decision-making of micro, small, and medium-sized enterprises (MSMEs) in West Java. Using a sample of MSME owners, the study employs multiple regression analysis to explore the relationships between these variables. The findings reveal that financial literacy is the most significant factor influencing financial decision-making, followed by perceived usefulness, risk tolerance, and trust perception. The results underscore the importance of financial education, adoption of beneficial financial tools, and fostering trust in financial institutions for enhancing MSME financial decisions. The study offers practical and theoretical contributions, providing valuable insights for policymakers, financial institutions, and MSMEs. Future research should consider expanding the geographical scope and exploring potential moderating factors in financial decision-making.